Spatial Crime Displacement in South Side Chicago : From the Projects to the 'Hood - Melsness, Dave (My University, 2011)
This project is a case study of the effectiveness of the Chicago Housing Authority?s revitalization efforts in creating new lower-crime/livable communities after the demolition of the Robert Taylor Homes in South Chicago. This study is premised on the concept of geographic displacement theory, which suggests that when governmental agencies attempt to eliminate crime by changing the local situation in which it occurs rather than eliminating crime, they move it to a different location.
Color poster with text, images, and maps
Keywords: Urban renewal--Illinois--Chicago--Case studies; Crime analysis--Illinois--Chicago; Crime--Illinois--Chicago; Public housing--Illinois--Chicago--Social aspects; Chicago (Ill.)--Social conditions; Crime forecasting--Illinois--Chicago; Posters